MENGEMIS DALAM PERSPEKTIF TAFSIR - Helfi, Helfi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2011)
How could if being a Moslem without the Qurâ€™an, it is inspiring in every aspect. It also opened the space layered intrepretation of each generation. Al Qurâ€™an is a baseless and endless sea. Al Qurâ€™an also talks about begging which for some people is a contemptible act. Allah emphasized people not to beg or ask too much with another. The only place to ask is just to almighty rich (Allah/God). The realization of the hard workâ€™s importance -without raise your hand to others- is exemplified by the Messenger of Allah (Allah). heâ€™s poverty (since childhood) does not make him a beggar. Hard work and optimism became an inseparable part of his pride. Disaster or calamity that given by God in any form, should not make a people be a a pessimist and beg the others without shame. Moreover, making the â€œbeggingâ€ as a sustainable productive enterprises in various ways.